The Armed Forces in the Constitution of the Republic of Chile - Cea Cienfuegos, Sergio; Morales, Patricio (Derecho Público Iberoamericano, 2014)
The authors describe the historic constitutional evolution of the Armed Forces showing, the legal regulation of the military institutions in the Constitution of 1980 and enunciate the need to maintain in the constitutional text a precise reference to those Institutions.